Efforts to Increase Archipelago Identity Awareness through Digital Collage Learning for Class XII 8 Students of SMA Negeri 13 Surabaya - Novia Eka Permata Sari; Setyo Yanuartuti; Choirunnisa Choirunnisa (Riviera Publishing, 2024)
In the current era of globalization, many students are experiencing a cultural identity crisis, where they are more likely to appreciate foreign culture than local culture. This phenomenon can be seen among students of SMA Negeri 13 Surabaya, where students' interest in the archipelago's cultural activities tends to be low. This study aims to increase awareness of the archipelago's cultural identity among students of class XII 8 SMA Negeri 13 Surabaya through digital collage learning. The method used is a cultural arts learning approach with the theme of the archipelago which is carried out in two cycles. Each cycle consists of planning, action, observation, and reflection stages. The results showed that students were not only able to complete the task well, but also produce quality collage works. There was a significant increase in students' understanding of the culture of the archipelago, which was reflected in the average pre-test score of 58 to 82 in the post-test. Some students even published their work on social media, indicating an increase in cultural awareness. This research is expected to be a reference for other teachers in developing art and culture learning methods that are more interesting and relevant to modern technology. The conclusion of this research shows that digital collage learning is effective in improving students' understanding of Nusantara culture. Students show active involvement in the learning process, which can be seen from students' activeness in the learning process.